Germination and Early Seedling Growth of High Andean Native Plants under Heavy Metal Stress - Parera, Victoria (2023)
The development of large-scale mining activity along the Central Andes of Argentina (CAA) has generated significant amounts of waste materials containing heavy metals. Phytoremediation is a promising eco-friendly, low-cost, and effective technology for the removal of heavy metals. The present study aimed to identify two native dominant species from the CCA, Adesmia subterranea and A. pinifolia, as metal-tolerant plant species for the first time, by evaluating the germination and early seedling growth at different concentrations (ppm) of Cd (3, 4.5 and 6), Ni (150, 225 and 300), As (20, 30 and 40), and Hg (0.8, 1.2 and 1.6) Early seedling growth was found to be more sensitive to heavy metals than germination. Ni and As exhibited the greatest inhibitory effect on both species’ germination percentages. In contrast, with Cd and Hg, no inhibitory effect was recorded. Root length, metal tolerance index, and fresh and dry weight were stimulated with Hg. However, the phytotoxic effect was greater as the concentration of Ni, As, and Cd increased. As an overall conclusion, the order of toxicity for these species can be classified as Ni > As > Cd > Hg. Therefore, Adesmia species could be considered as candidates for phytoremediation of soils contaminated with Hg and low concentrations of Cd.